Method for evaluating the characteristics of counter movement in jump exercises - Kajitani, R.; Maemura, H.; Yamamoto, K.; Seki, K.; Ogata, M.; Kigoshi, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2018)
The aim of this study was to examine the validity, reliability, and utility of a method for evaluating the characteristics of the counter movement jump. Fifty-two male track and field athletes (sprinters or decathletes) jumped from a 30-cm platform and consciously changed their counter movement times. This study determined the counter movement time required to achieve the highest jump. The results are summarized as follows: 1. The waveform between the counter movement time and jumping height was an inverted U-shape. 2. It is normally accepted that the optimum counter movement time is determined via the jump test. 3. There was a significant correlation between the first test and the re-test in terms of the counter movement time. 4. Participants were classified into 5 groups based on their optimum counter movement times and highest jumping heights. These results suggest that the newly developed jumping test discussed in this study is a valid method for evaluating the characteristics of counter movement.